PERMAINAN TEKA-TEKI SILANG SEBAGAI MEDIA DALAM PEMBELAJARAN BAHASA ARAB (MUFRADAT) - M. Khalilullah (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2012)
Teaching mufradat (vocabulary) in Arabic was usually taught by using sam’iyah syafawiyah that the students memorized the vocabularies given by the teachers. By using this method, it seemed that students felt bored in memorizing the vocabularies monotonously so that they have low motivation in learning. Pertaining to the phenomenon above, this writing will offer how to teach vocabularies to the students by using a game. Because the students are still in teenage-age who are fond of playing game, teaching by using a game will make them interested in learning that the values will indirectly be offered. The game meant in this writing is cross word that is usually used to spend a spare time has been used in teaching at schools. So, it can be used as a medium in teaching that wakes the neuron up and to refresh the mind to work optimally because it will make the mind relax in learning process. In teaching Arabic, it is rare used by the teachers even they do not understand that this game can be used to teach vocabularies in teaching mufradat (vocabularies).